The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/07853890.2021.1966087
|View full text |Cite
|
Sign up to set email alerts
|

Screening differentially expressed genes between endometriosis and ovarian cancer to find new biomarkers for endometriosis

Abstract: Aim Endometriosis is one of the most common reproductive system diseases, but the mechanisms of disease progression are still unclear. Due to its high recurrence rate, searching for potential therapeutic biomarkers involved in the pathogenesis of endometriosis is an urgent issue. Methods Due to the similarities between endometriosis and ovarian cancer, four endometriosis datasets and one ovarian cancer dataset were downloaded from Gene Expression Omnibus (GEO) database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
(83 reference statements)
0
11
0
1
Order By: Relevance
“…Furthermore, one of the tumor necrosis factor receptors, TNFRSF4, could be a useful target for immunotherapy of HNSCC [34]. Although there are no published reports on GAST and IGHM for HNSCC, these genes may be related to tumorigenesis and development [35,36]. In general, these previous findings emphasize the importance of these seven genes in HNSCC prognosis prediction.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, one of the tumor necrosis factor receptors, TNFRSF4, could be a useful target for immunotherapy of HNSCC [34]. Although there are no published reports on GAST and IGHM for HNSCC, these genes may be related to tumorigenesis and development [35,36]. In general, these previous findings emphasize the importance of these seven genes in HNSCC prognosis prediction.…”
Section: Discussionmentioning
confidence: 92%
“…IGHM is an immune-related gene encoding the C region of the µ heavy chain and defines its isoform ( 62 ). It significantly affects the density of infiltrating CD20 + B cells in tumor tissues ( 63 ). In addition, Pocha et al revealed that a high expression of surfactant genes, including SFTPB , was associated with intratumoral T-cell infiltration and a low immunosuppressive microenvironment in LUAD ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hope to find markers of tissue and blood coexistence for BRCA identification and diagnosis. Furthermore, we searched for “tissue-blood shared miRNAs as cancer biomarkers” regarding BRCA or other carcinomas, but there were only a few studies that focus on marker miRNAs that work in both tissues and blood [ 40 , 41 , 42 , 43 , 44 ]. Thereby, we hope to fill the gap of miRNAs shared by tissues and blood as tumor biomarkers.…”
Section: Introductionmentioning
confidence: 99%